(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2020)
As a result of a study of the mycobiota of the Dnistrovskyi Canyon National Nature Park (Ternopil Region, Ukraine), 337 species of fungi-like protists and fungi were found: 25 species belong to slime molds, 2 – to Zygomycota, 192 – Ascomycota and 118 – Basidiomycota. Four species Neocucurbitaria prunicola, Neomedicopsis prunicola, Polyscytalum neofecundissimum, and Roussoella euonymi, recently have been described by one of the authors as new to science. 21 species Acremonium domschii, Arachnocrea stipata, Bertiella rhodospila, Ceratostomella pyrenaica, Colletotrichum eryngiicola, Cosmospora arxii, Dialonectria diatrypicola, Fenestella media, Hypomyces subiculosus, Isaria fumosorosea , Massaria campestris, Nectriopsis oropensoides, Parafenestella rosacearum, Pseudocosmospora eutypae, P. eutypellae, P. hypoxylicola, Repetophragma inflatum, Stylonectria carpini, Thyronectria rhodochlora, Tolypocladium microsporum and Tympanosporium parasiticum, are new to Ukraine. Another 17 are rare species. Among them: Kavinia himantia, Mucronella calva and Xylobolus frustulatus are indicators of natural, well-preserved forests. Among collected fungi the vast majority are xylotrophic (181 species) and fungicolous (69 species). Other ecological groups remain poorly examined.